2-Chloro-N-(2,5-dichlorophenyl)acetamide - Gowda, B. Thimme (International Union of Crystallography, 2009)
The conformation of the N—H bond in the structure of the title compound, C(8)H(6)Cl(3)NO, is anti to the C=O bond. The N—H H atom shows close intramolecular N—H⋯Cl hydrogen bonds with both the ring Cl atom in the ortho position and the side-chain Cl atom. The molecules crystallize in planes parallel to (221).